2004
DOI: 10.1161/01.hyp.0000137305.77635.68
|View full text |Cite|
|
Sign up to set email alerts
|

Local Shear Stress and Brachial Artery Flow-Mediated Dilation

Abstract: Abstract-Endothelium-dependent flow-mediated dilation is a homeostatic response to short-term increases in local shear stress. Flow-mediated dilation of the brachial artery in response to postischemic reactive hyperemia is impaired in patients with cardiovascular disease risk factors and may reflect local endothelial dysfunction in the brachial artery. However, previous studies have largely neglected the effect of risk factors on evoked shear stress, which is the stimulus for dilation. We evaluated brachial ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
361
1
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 355 publications
(393 citation statements)
references
References 34 publications
24
361
1
7
Order By: Relevance
“…In clinical studies, it is generally assumed that the velocity profile is either flat or parabolic and that the BVF is proportional to the maximum velocity waveform [10,17,26,28,30]. It is widely believed that the Womersley profile approach [41], incorporating the pulsatile behavior of the BVF, delivers more physiological waveforms than the quasi-static (parabolic) Poiseuille profile approximation.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical studies, it is generally assumed that the velocity profile is either flat or parabolic and that the BVF is proportional to the maximum velocity waveform [10,17,26,28,30]. It is widely believed that the Womersley profile approach [41], incorporating the pulsatile behavior of the BVF, delivers more physiological waveforms than the quasi-static (parabolic) Poiseuille profile approximation.…”
Section: Introductionmentioning
confidence: 99%
“…Briefly, high‐resolution ultrasound was used to measure brachial artery diameter before and 1 minute after induction of hyperemic response by 5‐minute cuff occlusion of the upper arm. Doppler flow signals were recorded from the brachial artery before and after cuff occlusion to measure reactive hyperemia 21. Afterwards, we measured nitroglycerin‐mediated dilatation, which reflects non–endothelium‐dependent dilatation.…”
Section: Methodsmentioning
confidence: 99%
“…In a large cohort from Framingham, it was demonstrated that hyperemicinduced shear stress was an important predictor of brachial FMD. In addition, risk factors diminished the magnitude of shear stress, suggesting that a reduced stimulus explains the diminution in endothelial function in subjects with cardiovascular risk factors (122).…”
Section: Interrelationship Between Arterial Stiffness and Endothelialmentioning
confidence: 97%
“…Arterial stiffness has also been demonstrated to be related to brachial artery FMD vasodilation in a recent small study (121). And finally, a recently published study by Mitchell et al (122) has challenged our thinking about the effect of risk factors on brachial endothelial function. In a large cohort from Framingham, it was demonstrated that hyperemicinduced shear stress was an important predictor of brachial FMD.…”
Section: Interrelationship Between Arterial Stiffness and Endothelialmentioning
confidence: 99%